(untitled) (El-Wahat Journal for Research and Studies, 2025)
Proverbs, Often Considered Gems Of Popular Wisdom, Play A Crucial Role At The Heart Of Every Society. These Short Expressions, Passed Down From Generation To Generation, Are Much More Than Simple Linguistic Formulas. They Embody The Quintessence Of Collective Experience And Know-How Accumulated Over Time. The Importance Of Proverbs In Society Lies In Their Ability To Encapsulate Universal Truths, Convey Moral Teachings, And Offer Practical Advice. As A Traditional Society, Soufi Society Is No Exception To The Rule And Is Also Full Of Thousands Of Proverbs. This Article Offers An Analysis Of Soufi Proverbs, Their Status And Their Future. Keywords: Proverb, Culture , Society , Orality , El-Oued